Ileal Adenocarcinoma with Liver Metastasis in Patient with Crohn’s Disease: A 9-Year Survival - Jiten P. Kothadia; Deepa H. Nagaraju; Seymour Katz; Howard Bruckner; Steven H. Itzkowitz; Myron Schwartz (Case Reports in Oncological Medicine)
Small bowel adenocarcinoma is a rare but well-known complication of Crohn’s disease. The diagnosis of small bowel adenocarcinoma remains difficult since its presentation is highly variable and mimics active or obstructive Crohn’s disease. The diagnosis is often delayed and typically detected only at surgery in an advanced stage with a poor prognosis. We report a case of metastatic ileal adenocarcinoma in a patient with Crohn’s disease with prolonged survival. Our case describes serial promising treatment options of these advanced malignancies and raises a possible role for checkpoint immunotherapy.